1993
DOI: 10.1254/jjp.61.157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BMY-21502 on Anoxia in Mice

Abstract: piperidinyl]methyl]-2-pyrrolidinone) against cerebral anoxia were investigated using various models in mice, in comparison with those of other cerebroactive drugs. Oral administration of BMY-21502 (10-100 mg/kg) significantly prolonged the survival time in KCN (2.4 mg/kg, i.v.)-induced anoxia. Oxiracetam and idebenone exerted similar but weak protection at doses above 100 mg/kg, p.o. and only at a dose of 100 mg/kg, p.o., respectively. Significant protection by BMY-21502 against moderate hypobaric hypoxia was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…24,25) The presynaptic terminals of the cholinergic neuron are vulnerable to ischemic insult, and cholinergic dysfunction precedes postsynaptic CA1 pyramidal cell death in the hippocampus. 16) Consequently, in order to confirm whether sinapic acid directly modulates the cholinergic function, its effect on scopolamine-induced amnesia was examined.…”
Section: Discussionmentioning
confidence: 99%
“…24,25) The presynaptic terminals of the cholinergic neuron are vulnerable to ischemic insult, and cholinergic dysfunction precedes postsynaptic CA1 pyramidal cell death in the hippocampus. 16) Consequently, in order to confirm whether sinapic acid directly modulates the cholinergic function, its effect on scopolamine-induced amnesia was examined.…”
Section: Discussionmentioning
confidence: 99%
“…These two experimental models are generally used to screen drugs for cerebrovasucular diseases; such drugs include activators of cerebral energy metabolism (14,15), cerebral vasodilators (15 -17), CNS depressants (18,19) and activators of the CNS cholinergic system (20) or acetylcholine esterase inhibitors (21,22). In the two models, BHB significantly prolonged the survival time at the dose of 50 mg路kg -1 路h -1 or more, while glycerin failed in all models.…”
Section: Discussionmentioning
confidence: 99%
“…16) Our data show that compound 1 suppresses the breakdown of cellular metabolism induced by the inhibition of cytochrome oxidase. Gibson et al reported that KCN reduced potassium-stimulated synaptosomal acetylcholine release.…”
Section: Discussionmentioning
confidence: 65%